Selection of potential non-Sacharomyces probiotic yeasts from food origin by a step-by-step approach - Rodriguez, Pilar Fernandez-Pacheco; Arevalo-Villena, Maria; Rosa, Isabel Zaparoli [UNESP]; Perez, Ana Briones (Elsevier B.V., 2018)
Due to healthcare is increasing in nowadays, the use of the commercial probiotics is in progress and each day they are more demanded. The challenge of this study is to identify yeast species for using as probiotic organisms. Thus, the research applied a step-by-step approach, to study the probiotic potential of non-Saccharomyces yeast strains. The 215 yeasts were isolated from different environments such as wineries, oil mills, brines cheeses, fermented vegetables and distilleries in previous works and were identified to strain level by RAPD-PCR technique resulting 108 different strains. A general screening was carried out to know the probiotic capability of the yeasts, following the next steps: study of the ability to resist and grow of the yeasts when they exposed to simulated in vitro digestion conditions and influence of time, temperature, pH and the presence of enzymes on the kinetic growth parameters (lag phase (lambda), generation time (G), maximum OD (ODmax) and the specific growth rate constant (mu(max))). The results made possible the selection of the 23% of the strains and they were assayed for knowing their capability of self-aggregation and hydrophobicity. Biofilm formation capacity and viability after simulated sequential salivary-gastric-intestinal digestion were then studied for the 10 best strains. Statistical analyses were applied in each step to make the selection. The final results showed that two yeasts, H. osmophila and P. kudriavzevii, were the most promising strains.
Keywords: Non-Saccharomyces; Probiotic yeasts; Gastrointestinal resistance; Auto-aggregation; Hydrophobicity; Biofilm